101 nutty nature jokes - Berger, Melvin; Taylor, B. K. (New York : Scholastic, 1994)
A collection of jokes about animals and nature.
Keywords: Animals -- Juvenile humor; Nature -- Juvenile humor; Riddles, Juvenile; Wit and humor, Juvenile